Influencia del potasio en la resistencia de los tejidos de arroz al ataque de Pyricularia oryzae Cav. - Moscol Riofrío, L.; Morales Abanto, A. (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2025)
The relation between 5 levels of potassium (1170, 1750, 2340 2920, y 3510 ppm), foliage tissue resistance and rice panicle resistance to the action of Pyricularia oryzae Cav. was studied. Plants height and dry residue was too considered. Two inoculations were made. The first to the foliage (160 days old) and the second to the panicle neck (12 days later). The conditions were 100 per cent relative humidity and 25°C temperature. The results suggest tha the plants with higher levels of potassium are more resistant to Pyricularia oryzae cav. than those with lower levels. The plant´s height and dry residue showed a significative linear tendency.